Assessing Effects of Covid-19 Responses on Mental Health in Malawi (Report) - Ndasauka, Yamikani (University of Malawi, 2022)
The Coronavirus Disease (Covid-19) pandemic has overwhelmed health systems in all countries, especially those in the least developing countries, Malawi included. As such, this project sought to investigate the effects of Covid-19 responses on mental health in Malawi in terms of perception toward mental health in general, the mental health of adolescents and health workers and mental health services. The project had three main phases, research, awareness campaign and dissemination. The study found a massive influence of culture and religion on perceptions of people with mental health. Mental health is primarily understood from cultural and religious beliefs. Further, the study found that providing mental health services amidst the pandemic has strained the already pressed and neglected health sector. On the effects of Covid-19 on the mental health of frontline health workers, the study found a high prevalence of Covid-19 related depression (31.2%, n=109), anxiety (30.3%, n=109) and PTSD (24.8%, n=109) among healthcare workers. The study also found significantly more healthcare workers with depression (36% VS 16%, P=0.06), anxiety (38% vs 1%, P<0.01), and PTSD (30% vs 8%, P=0.03) in referral hospitals compared to district hospitals. In addition, the study found that overall, 22%, 21% and 23% of the adolescent respondents had Covid-19-related depression, anxiety and PTSD. The project implemented awareness campaigns in the four districts: Lilongwe, Mangochi, Karonga, and Zomba. These awareness campaigns aimed to increase awareness of Covid-19 and its effects on mental health. The awareness campaigns in Zomba and Lilongwe were in the form of Talk-Shows, where speakers were given 10 minutes of presentation which covered the following topics; Introduction to mental Health, Mental Disorders, risk factors of Mental disorders, ways of coping with mental health problems and service providers for mental health services. In Karonga, the project targeted secondary school-going adolescents and was conducted as a variety show which saw students showcase different activities like poems, dances, songs, and drama. In Mangochi, the campaign took place for two days. The first day consisted of mental health training for Health Surveillance Assistants (HSAs). On the second day, the awareness campaign was conducted in the community, utilising theatre for development, where community leaders, men, women, and youths were engaged in raising mental health awareness through their play. In all the campaigns, participants were given different mental health IEC materials. The project is disseminating the project and study outcomes by publishing three policy briefs, media coverage, five academic publications, an edited book, and five conference presentations. Aside from increasing engagement with key stakeholders, including health practitioners, policymakers, lawmakers, academia, and government officials, on mental health issues and Covid-19, the project has reached more than 100,000 people through awareness campaigns, radio jingles, and IEC materials, to pay more attention to early signs of mental health problems, prevention and coping strategies and to deal away with the stigma associated with people suffering from mental health problems.
Covid-19 and Mental Health in Malawi Report
Keywords: Covid-19; Mental Health; Malawi; Covid-19 Responses